The Business Environment in Cee Countries: Current Challenges and Perspectives - Valentina Diana Rusu; Angela Roman (CES Working Papers, 2016)
The Central and Eastern European countries have experienced significant imbalances starting with 2008 that have affected their business environment profoundly. Thus, the firms operating in the region have faced, and continue to face, difficulties and major challenges. Through this paper we aim at analyzing the key indicators that characterize the business environment of a country, and by analyzing their values through time, we want to compare the situation from ten countries from CEE. We analyzed the indicators for a period of eight years, between 2007 and 2014. This period presents interest because it comprises the period of the recent financial crisis. By using indicators characterizing the business environment we analyze the ease of doing business, but also the ease of getting credit, domestic credit to private sector and reforms adopted in order to improve the access to credit by the CEE countries. We also analyze the time needed to start a business and the regulations regarding start-ups, which may encourage or discourage the new firms to enter the market. The results obtained show that the CEE countries are starting to recover from the current financial crisis, but are still lagging behind the developed countries of the European Union. However, the business environment has registered a series of improvements in the majority of the analyzed countries in the last two years, improving especially the areas of starting a business, getting a credit and paying taxes.
Keywords: G32; O16; 330; business environment; CEE countries; doing business; legal rights index; getting credit; financial crisis; reforms